The economywide impacts and risks of Malawi’s farm input subsidy program - Arndt, Channing; Pauw, Karl; Thurlow, James (Wiley, 2016)
We estimate the impact of Malawi's Farm Input Subsidy Program using an economy‐wide approach. This approach yields benefit‐cost ratios about 60% higher than existing partial equilibrium studies, a result of our accounting for indirect benefits. Fertilizer response rates remain the determining parameter for benefit‐cost ratio levels. Even with lower‐end response rates, the program is pro‐poor and generates double‐dividends through higher and more drought‐resilient yields. Overall, for macro‐economically significant programs, our approach strongly complements survey‐based evaluations. For Malawi, our results buttress arguments for a focus on program improvements.